+0  
 
0
89
1
avatar
(2x+1)/3 + 7 = (3x-1)/4
Guest Jul 9, 2017
edited by Guest  Jul 9, 2017
Sort: 

1+0 Answers

 #1
avatar+4692 
+1

\(\frac{2x+1}{3}+7=\frac{3x-1}{4}\)                                      Multiply both sides of the equation by  4  .

 

\(4\,*\,(\frac{2x+1}{3}+7)=3x-1 \\~\\ \frac{4(2x+1)}{3}+28=3x-1\)                        Distribute the  4  .

 

\(\frac{8x+4}3+28=3x-1 \\~\\ 3\,*\,(\frac{8x+4}3+28)=3\,*\,(3x-1) \\~\\ 8x+4+84=9x-3\)          Multiply both sides of the equation by 3 and distribute.

 

\(8x+88=9x-3\)                                    Subtract  8x  from both sides of the equation.

 

\(88=x-3\)                                                Add  3  to both sides of the equation.

 

\(91=x\)

 

 

Notice that we could have multiplied both sides by  12  to begin with and this would get rid of both fractions in one step. smiley

hectictar  Jul 9, 2017

18 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details